A case of aggressive giant dermatofibrosarcoma protuberance occurring in the parotid gland. (2019) - Adilbay, Dauren; Khozhamkul, Fariza; Toiynbekova, Samal; Ahmetov, Daniar
Highlights: The parotid region is a very rare site with few published case reports, shares the common features of trunk DFSP. Radiotherapy or chemoradiotherapy can be applied to large and recurrent cases, but with unclear benefit. Dermatofibrosarcoma protuberans is a rare tumor, with infiltrative margins, high local recurrence rate, and rare distant metastasis. CD34 immunohistochemistry is a reliable marker for difficult diagnostic cases. Abstract: Introduction: Dermatofibrosarcoma protuberans (DFSP) is a cutaneous malignancy that arises from the dermis and invades deeper tissue. The cellular origin of DFSP is not clear. Evidence supports the cellular origin being fibroblastic, histiocytic, or neuroectodermal. Presentation of case: A 38 years old, women presented with slow-growing large right parotid mass. A total parotidectomy performed with auriculectomy and reconstruction using ALT flap. Diagnosis confirmed by pathology and immunohistochemistry. Tumor recurred in 10 months, the second surgery with subsequent chemoradiotherapy performed. Patient initially treated with wide resection, 4 cycles of chemotherapy and postoperative radiotherapy 40 Gy, with the recurrence in 10 months. We performed a second surgery followed by radiotherapy. She is disease-free for more than two years under follow-up. Discussion: The main treatment of DFSP is surgical resection with wide negative margins or Moh's surgery. Advanced cases treated with addition of radiotherapy or chemoradiotherapy, but with unclear benefits. In our case, huge tumor located in the parotid region recurred after initial surgery and adjuvant treatment. Conclusion: Clinically, DFSP usually manifest as well circumscribed, slow-growing, smooth, and painless masses. In cases with advanced tumor in parotid region, recurrence may occur despite aggressive initial treatment with wide resection and chemoradiotherapy.